Pengaruh Pembelajaran PBL (Problem Based Learning) terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Khoirun Nisak; Adha Istiana (Universitas Indraprasta PGRI, 2017)
The purpose of this reseacrh is to know whether there is influence of problem based learning model of learning ability to solve student mathematical problem. The problem solving ability in this research is students’ ability to solve contextual problem in matrix material. Method in this research is quantitative research by using Quasi Experiment analysis and experiment design (One group P-retest-posttest design). The population in this study is all students of SMK in Ngunut with samples taken is class X department of administration office. Technique of collecting data that is used by giving test description from pre-test and post-test. Testing requirements analysis of this data is a test or normality. The data test results show normal data. To test the hypothesis using Paired Samples Test with the help of SPSS, and the result of Paired Samples Test from SPSS output shows niali t arithmetic equal to -17,346 with significant 0,000. Because significant 0.000 <0,05 hence can be concluded that H_1 accepted, meaning there is significant influence of Problem Based Learning (PBL) model to ability of problem solving mathematics problem of student of class X in SMK Ngunut.